AVALIAÇÃO DA REATIVIDADE ÁLCALI AGREGADO DE ROCHAS VULCÂNICAS DO RIO GRANDE DO SUL - Costa, Luana C.; Bonsembiante, Francieli F. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The aggregate alkali reaction (AAR) is a chemical reaction that leads to the deterioration of concrete structures. It occurs between the concrete constituents (reactive aggregates and alkaline hydroxides present in the cement), in the presence of humidity, causing cracking, loss of strength as well as reduction of the useful life of the structures. Over the years many studies have shown the importance of knowing the reactivity of the aggregates, in order to take measures, when necessary, to mitigate the AAR. In view of this context, the objective of the present study is to evaluate the reactivity of volcanic aggregates of Rio Grande do Sul (RS). In order to reach this objective, 9 specimens of aggregates distributed throughout the northern half of RS, where the volcanic rocks were present, were collected. To evaluate the alkaliaggregate reactivity the accelerated test of the mortar bars (NBR 15577 part 4) was carried out. Of the results, ply one sample can be classified as "non-reactive". The test also showed that some specimens have greater potential for expansion than others, assuming the need for effective mitigation measures of the RAA.